Antioxidant and Antibacterial Test On Kombucha Tea Varian Pedada (Sonneratia caseolaris) - Fitriyani, Nur Lu'Lu; Prastiwi, Dani; Anindhita, Metha Anung; Rini, Septiyani Nanda; Silviana, Wanda (Babali Publisher, 2024)
Introduction: Kombucha tea is a health drink that can detoxify, antioxidant, energy source and boost the immune system. Kombucha has many variations in taste, including variations in adding fruit such as strawberries, apples, and peaches. Another variant of kombucha with added spices such as ginger and cinnamon. Pedada as a mangrove fruit that is widely available in coastal mangrove forests has potential as a food ingredient because it has very good nutritional content. The aims of this research is to tests of antibacterial effectiveness and antibiotic content from pedada variant of kombucha as a health drink. Methods: the research design is pure experimental research with a completely randomized design. Making kombucha variant pedada through two stages of fermentation. Results: Primary fermentation was carried out for 12 days to produce kombucha tea and secondary fermentation was carried out for 4 days with the addition of variations of pedada fruit juice with concentrations of 0%, 10%, 20%, 30%, 40%. The antioxidant test results showed that the kombucha variant pedada contains antioxidants in the presence of tannins, saponins and flavonoids in kombucha pedada variatiant. Conclusion: The Kombucha pedada variant also has antibacterial activity on E. coli and S. thypi bacteria. The antibacterial activity of E.coli showed higher results than chloramphenicol, while S. thypi showed lower effectiveness than chloramphenicol.